Of the available triptans, which should be chosen and how should they be used? - Valença, Marcelo Moraes; Rosas, Emanuela Paz; Costa, Raisa Ferreira; Silva, Amanda Araújo da; Ferreira, Maria Rosana de Souza; Reis, Rita Santana dos; Valença, Marcelo Andrade; Andrade- Valença, Luciana Patrízia Alves de (Headache Medicine, 2019)
There is a plethora of articles dealing with the use of triptans to treat migraine, but so far no unanimity exists regarding the optimal form of using this group of drugs in a patient with recurrent attacks of migraine. Although all of them may exert their pharmacological effects through a known specific mechanism of action, i.e. agonist effects on serotonin 5-HT (1B/1D) receptors, distinct differences exist. The author comment a few facts on the prescription of triptans and possible adverse effects, depending on the clinical scenario. Thus, even though an enormous amount of information has accumulated over the last few decades on triptans, several questions remain to be answered, and research priorities need to be addressed.